Proteome‐Wide Mendelian Randomization Identifies Therapeutic Targets for Abdominal Aortic Aneurysm - Ka Zhang; Yuan Liu; Aiqin Mao; Changzhu Li; Li Geng; Hao Kan (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2025)
Background The proteome is a key source of therapeutic targets. We conducted a comprehensive Mendelian randomization analysis across the proteome to identify potential protein markers and therapeutic targets for abdominal aortic aneurysm (AAA). Methods and Results Our study used plasma proteomics data from the UK Biobank, comprising 2923 proteins from 54 219 individuals, and from deCODE Genetics, which measured 4907 proteins across 35 559 individuals. Significant proteomic quantitative trait loci were used as instruments for Mendelian randomization. Genetic associations with AAA were sourced from the AAAgen consortium, a large‐scale genome‐wide association study meta‐analysis involving 37 214 cases and 1 086 107 controls, and the FinnGen study, which included 3869 cases and 381 977 controls. Sequential analyses of colocalization and summary‐data‐based Mendelian randomization were performed to verify the causal roles of candidate proteins. Additionally, single‐cell expression analysis, protein–protein interaction network analysis, pathway enrichment analysis, and druggability assessments were conducted to identify cell types with enriched expression and prioritize potential therapeutic targets. The proteome‐wide Mendelian randomization analysis identified 34 proteins associated with AAA risk. Among them, 2 proteins, COL6A3 and PRKD2, were highlighted by colocalization analysis, summary‐data‐based Mendelian randomization, and the heterogeneity in an independent instrument test, providing the most convincing evidence. These protein‐coding genes are primarily expressed in macrophages, smooth muscle cells, and mast cells within abdominal aortic aneurysm tissue. Several causal proteins are involved in pathways regulating lipid metabolism, immune responses, and extracellular matrix organization. Nine proteins have already been targeted for drug development in diabetes and other cardiovascular diseases, presenting opportunities for repurposing as AAA therapeutic targets. Conclusions This study identifies causal proteins for AAA, enhancing our understanding of its molecular cause and advancing the development of therapeutics.